SCIENTIFIC FOUNDATIONS OF THE RATIO OF GENERAL AND SPECIAL PHYSICAL TRAINING IN THE INITIAL TRAININ - J.N. Eshpulatov (International Journal of Literature and Language Studies, 2026)
This article analyzes the scientific and pedagogical foundations of the optimal ratio between General Physical Training (GPT) and Special Physical Training (SPT) at the initial stage of sports preparation. The research is based on the theory of sports training, the laws of physiological adaptation, and the developmental characteristics of young athletes. The functional content of GPT and SPT, their influence on the athlete’s organism, and the principles of gradual load progression are scientifically substantiated. The results of the study indicate that the predominance of GPT at the initial stage is a key factor determining the effectiveness of an athlete’s future specialized preparation.